Topological optimization of biomimetic sandwich structures with hybrid core and CFRP face sheets. (12th April 2017) - Sun, Zhi; Li, Dong; Zhang, Weisheng; Shi, Shanshan; Guo, Xu
Abstract: Porous-core sandwich structures with CFRP face sheets have similar micro structures to biological tissues, for example, grass leaves. The sandwich structures are composed of two thin, stiff face sheets, which provide the primary in-plane structural stiffness, and a thick low-density porous core, which provides the functionalities and the majority of out-plane stiffness. However, the mechanical properties of these sandwich structures are often limited by local failures such as face-core debonding or core collapse. Inspired by the tree leaves with fractal distributed veins, which are larger and stiffer than grass leaves, in this paper, a topological optimization on the micro structures of core is conducted to achieve exceptional mechanical properties. By taking adhesive-area constraint, local-buckling constraint and embedding-volume constraint into consideration, a biomimetic hybrid core, which is similar to the fractal distribution of tree veins, is found to be an optimal core design for sandwich structures with CFRP face sheets.